The Vector Entomology Index of Dengue Hemorrhagic Fever (DHF) was conducted in the Working Area of the Temindung Health Center: Study on the Guerilla Street - Daramusseng, Andi; Hanif Abdi Rahman, Dimas (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the Dengue virus. The virus can be transmitted through Aedes sp. The Aedes mosquito's life cycle undergoes a complete metamorphosis, starting with the egg-larva-pupa-adult mosquito. Larval density can be a contributing factor to a high risk of dengue transmission in the community. This study aimed to determine the entomological index of dengue hemorrhagic fever vectors on Gerilya Street, Sungai Pinang Dalam Village, Samarinda City. The research design used an observational method with a cross-sectional approach. The number of samples is 100. The data were analyzed using the DHF larva population indicator approach, namely the House Index (HI), Container Index (CI), Breteau Index (BI), and Density Figure (DF). The rIt was found that the entomological index on Jalan Gerilya in Kelurahan Pinang Dalam Kota Samarinda had HI values of 50% (DF 7), CI values of 23.3% (DF 6), and BI values of 164% (DF 7). I, CI, and BI values are included in the high-risk transmission category. Immediate control efforts are needed to prevent an increase in dengue transmission.